Impact of dietary supplementation of L-citrulline to meat goats during gestation on reproductive performance - Makenzie G. Newton; Arianna N. Lopez; Claire Stenhouse; Karina L. Hissen; Erin D. Connolly; Xingchi Li; Lan Zhou; Guoyao Wu; William B. Foxworth; Fuller W. Bazer (Journal of Animal Science and Biotechnology)
Abstract Background Meat goat production is a worldwide industry with products such as meat, milk, soap, and fiber being produced. There are approximately 2.6 million meat goats in the United States. For breeding female ruminants, early pregnancy loss is estimated to be 30% within the first month of gestation. Extracellular L-citrulline (a precursor to L-arginine) is not degraded by ruminal microbes due to the lack of uptake. L-Arginine and thus L-citrulline, have beneficial impacts on placentation and, subsequently, fetal-placental development and survival. This study aimed to determine the impact of feeding L-citrulline to meat goats during gestation to improve reproductive success. Meat goats were fed either a control (CON) or L-citrulline (CIT) supplemented diet from d 12 to 82 of gestation. Blood samples were collected and sera were subjected to high-performance liquid chromatography analyses to quantify the abundance of amino acids. Pregnancy rates were determined on d 30, 61, and 90 of gestation, and litter weight, individual birth weights, and 90 d adjusted weaning weights were collected. Results The concentrations of citrulline, ornithine, and arginine were greater in CIT does compared to CON does, but there was no difference in pregnancy rates between CON and CIT does. Birth weight was greater for male kids born as singles when compared to females, but this phenotype was not observed for kids born as twins or triplets. Further, males born to CON does had greater 90 d adjusted weaning weights than females, but this was not observed in the CIT group. Female kids born to CON and CIT Boer goats had heavier 90 d adjusted weaning weights than those born to Spanish or F1 Boer-Spanish does. Conclusion This study provides proof of concept that feeding dietary L-citrulline increases concentrations of citrulline and arginine in blood of gestating meat goats. However, further studies are needed to understand the cellular mechanisms impacted by feeding this supplement. Regardless, this study demonstrated that feeding L-citrulline has the potential to increase reproductive performance in gestating ruminants.